Assessing the Interplay of Epidemic Anxiety, Religious Coping, Spiritual Well-Being, and Tranquility During COVID-19 - Nimet Göknur Gözen; Süleyman Kahraman (Değerler Eğitimi Dergisi)

(untitled)
This study examines the relationships among epidemic anxiety, religious coping (positive and negative), spiritual well-being, and tranquility during the COVID-19 pandemic. Additionally, the study investigates potential differences in these variables based on gender and age. The sample consisted of 405 participants. The data is collected using the Epidemic Anxiety Scale, the Religious Coping Scale, the Spiritual Well-Being Scale, and the Tranquility Scale. The findings reveal a positive and significant relationship between epidemic anxiety and both positive and negative religious coping, but no significant relationship with overall spiritual well-being or tranquility. Examining the subscales, positive and negative religious coping are positively and significantly associated with spiritual well-being. The study finds a weak negative relationship with tranquility and negative religious coping. Crucially, a significant positive relationship between spiritual well-being and tranquility is discovered. These results were discussed within the existing literature, highlighting the complex interplay between epidemic-related anxiety, religious coping mechanisms, spiritual well-being, and the experience of tranquility during the COVID-19 pandemic. Moreover, the implications for supporting individuals' well-being during public health crises are considered.